Pediatric anosmia: A case series. (July 2018) - Hauser, Leah J.; Jensen, Emily L.; Mirsky, David M.; Chan, Kenny H.
Abstract: Introduction: Little is known about the etiology of olfactory dysfunction in the pediatric population. The aim of this study is to characterize the etiology and clinical features of anosmia and to explore evaluation options in a pediatric population. Methods: Olfactory dysfunction was identified at a tertiary pediatric hospital between January 2003 and October 2014 using a text-based and ICD-9 search of the electronic health record system. Clinical information gathered included history, physical examination and imaging study. A phone questionnaire was completed to determine persistence and development of other rhinologic, endocrine, or neurologic symptoms. Results: 37 children (male/female = 17/20) with mean/median ages of 13.28/14. 19 years were identified. The distribution of etiology was: rhinologic disease (N = 16), congenital (N = 4), trauma (N = 1), neoplasm (N = 1) and unknown (N = 15). Rhinologic disease included chronic rhinosinusitis (N = 3) and other nasal anatomic lesions. None of the four subjects with congenital anosmia had classic Kallmann syndrome. The utility of imaging in confirming an etiology of anosmia was noted in 1 of 8 CT and 5 of 22 MRI. The most significant finding of the questionnaire was confirmation of normal puberty in the congenital group. Conclusion: Similar to the adult population, rhinologic disease is the most common cause. Absence or hypoplasia of the olfactory bulbs without associated delayed puberty is the presentation of congenital anosmia in our cohort. MRI had a higher utility than CT in evaluating anosmia in general and congenital anosmia in specific. MRI to evaluate children with a history of congenital olfactory dysfunction is recommended.